Bacteria‐Inspired Aqueous‐in‐Aqueous Compartmentalization by In Situ Interfacial Biomineralization. Issue 2 (22nd December 2022) - Yuan, Hao; Li, Fei; Jia, Lufan; Guo, Ting; Kong, Tiantian; Meng, Tao
Abstract: Compartmentalization is essential for living cells to orchestrate their biological processes with controlled external influences. Thus, compartmentalization has been a constant theme for cell‐mimicking materials. Despite recent advances in engineering compartmentalized materials as synthetic cells and organelles, it remains difficult to produce robust and well‐ordered compartments with secluded environments in aqueous surroundings. Nature creates hierarchically ordered compartmentalized materials by utilizing bio‐catalyzed mineralization, inspired by which, mechanically robust all‐aqueous compartments are developed by engineering a mild biomimetic mineralization at aqueous/aqueous interfaces. The enzyme‐induced biomineralization generates a layer of densely‐packed particles, acting as an armor to enclose aqueous interiors. This strategy of in situ bio‐synthesized compartments is different from current strategies, where compartments are constructed by randomly adsorbed particles at interface, leading to inadequately controlled properties of compartments. To demonstrate the robustness and adaptiveness of the in situ bio‐synthesized all‐aqueous compartments, these are utilized as drug delivery materials by sequestering protein drugs at their aqueous interiors and releasing when exposing to gastric environments. The study provides new ways to fabricate compartmentalized materials with well‐defined properties, unlocking routes to the next generation of self‐assembled materials and structures by integrating aqueous two‐phase systems with biomineralization. Abstract : A story of bio‐compartments: mimicking the bacteria uratolytic pathway, the robust all‐aqueous bio‐compartments are developed by in situ synthesizing densely packed particles at the interface of aqueous two‐phase systems (ATPS). The resultant compartments show the strengthened interfaces and well‐defined properties for regulating the in‐and‐out of substances, which paves the way for fabricating the next generation of self‐assembled biomimetic materials.